EFFECTS OF COMBINED PHYSICAL TRAINING IN RISK OF FALLS IN THE ELDERLY (Fiep Bulletin - online, 2012)
The growth of life expectancy and of the elderly population increases the profiles of morbidity and mortality, with increased prevalence of chronic diseases and events that can have serious consequences to the health of the elderly, such as falls. The study aimed to evaluate the influence of combined physical training on balance and risk of falling in older adult participants in a physical activity program for old adults in Guarapuava-Pr. This study was characterized as pre experimental. Twenty-seven subjects participated in the study, with an average age of 64.9 ± 2.9 years of age and body mass index of 30.3 ± 7.1 kg/m². The risk of falling and balance were assessed using the Timed Up and Go test, before and after a combined physical training program, composed of resistance exercises, aerobic and stretching exercises for 60 minutes, 3 times a week, during a period of 12 weeks. The training was conducted with the use of resistance machines and free weights, consisting of 12 exercises for major muscle groups, from 1 to 3 sets of 10 to 15 repetitions. Aerobic training consisted of aerobic dance lasting 20 minutes and 10 minutes of stretching at the end of the session. To characterize the sample, data were analyzed using descriptive statistics and the Student’s t test for repeated measures after verification of normality and homogeneity, considering the significant difference p ? 0.05. The results demonstrated a significant decrease between pre and post test in the Timed Up and Go tests (11.96 ± SDs and 9.9 s, respectively). Regarding the risk of falling, there was an increase in the percentage of seniors classified as low risk and a decrease in the average risk (65% to 25% and 35% to 75%, respectively). Thus, we can conclude that the combined exercise training program may have brought benefits to participants, providing positive changes in their balance and, consequently, in the reduction of the risk of falling.
Keywords: older adults; physical training; balance; risk of falling